Electrical faults and their effects on induction machines (Journal of Academic Research, 2020)
Induction machines are commonly used as "backbones" in industrial applications and power systems. Although these devices have high reliability, they are usually subject to abnormal operating conditions that may lead to parameter changes. In this paper, effects of some electrical faults, open-circuit and short-circuit faults, on induction machine parameters are discussed in detail. It has been shown that, the envelope produced in stator currents has a different profile and frequency depending on the fault location. These effects can be used when monitoring the condition of the machine to reduce the time required to diagnose the malfunction. MATLAB SIMULINK is used to analyse and simulate the induction machine under both healthy and faulty conditions.
Keywords: Induction machines; condition monitoring; fault diagnosis